(untitled) (Ustozlar uchun, 2026)
There are no accidental turns in the history of sports. Every major victory is the product of years of accumulated mistakes, systemic changes, and decisions made with cold blood. The Uzbekistan national football team’s qualification for the 2026 FIFA World Cup was the final result of escaping long-standing utopian views and transitioning to real, pragmatic football. This process is not mere luck, but the triumph of precise calculation, a correctly chosen strategy, and discipline on the pitch. The wait of over 30 years, painful blows, and generational shifts finally united at a single point – the pillar of efficiency. Below, we will examine the fundamental factors, the chronology of falls, and recoveries that ensured this historical result through facts and systemic analysis.